P3_8 Elastic Launch - Kuzemczak, Jacek; Houghton, Kate; Clark, Ashley; Simms, Henry (Physics Special Topics, 2012)
<!– @page margin: 2cm P margin-bottom: 0.21cm; direction: ltr; color: #000000; widows: 2; orphans: 2 P.western font-size: 12pt; so-language: en-GB P.cjk font-size: 12pt; so-language: en-US P.ctl font-size: 12pt A:link color: #0000ff A.cjk:link so-language: zxx A.ctl:link so-language: zxx –> This is a brief investigation into the energetics of using a stretched elastic based slingshot to launch objects into space. The energy required to reach escape velocity is used to calculate some parameters of a theoretical elastic material that would be used to store the energy. It is found that for an acceleration distance of 828 m a spring constant of 4.01x106 Nm-1 would be needed to provide the 15385g acceleration.